Parietal closure in the abdomen controlled open Presentation of a technical resource - Torterolo, Edgardo; Neirotti, Rubens; Berriel, Edgardo (Cirugía del Uruguay, 1996)
A without tightness wa/1 e/asure technique is presented, maked by means of combined unloading incisions, at nivel of externa/ abdominal ob/ique and transversus abdominis. The authors refrained its application with success in two patient, with controlled open abdomen for abdominal sepsis, after determined the infectious focus.